2014
DOI: 10.1007/s00244-013-9989-y
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Comparison of Chlorinated Contaminant Concentrations and Profiles in Wild Terrestrial Mammals from Northwest Poland

Abstract: The aim of this study was to determine residual polychlorinated biphenyls (PCBs) and organochlorine pesticides in the adipose tissue of wild terrestrial mammals coming from the same area in northwest Poland and to compare the organochlorine content and profile between species. The study was performed on five mammalian species, including omnivores (badger, wild boar, raccoon dog) and herbivores (roe deer, red deer). The obtained results show that the levels of residues of most of the analyzed compounds were gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 42 publications
4
10
1
Order By: Relevance
“…The pattern of HCHs reported in this study (c-HCH P b-HCH ) a-HCH) is consistent with published reports on HCH patterns in different matrices and environmental media from Croatia (Kljaković -Gašpić et al, 2010;. In contrast, other reports for different carnivore species worldwide show that b-HCH, due to its persistency, is usually the highly dominating isomer (Bernhoft et al, 1997;Bentzen et al, 2008b), while dominating levels of a-HCH in tissues of wild animals were measured only in areas close to land in agricultural use, where technical mixtures of HCHs were used recently (Tomza-Marciniak et al, 2014). Christensen et al (2005) also reported domination of several more volatile pesticides, including P HCH and HCB, in contaminant profiles of interior grizzly bears consuming a higher proportion of terrestrial vegetation.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The pattern of HCHs reported in this study (c-HCH P b-HCH ) a-HCH) is consistent with published reports on HCH patterns in different matrices and environmental media from Croatia (Kljaković -Gašpić et al, 2010;. In contrast, other reports for different carnivore species worldwide show that b-HCH, due to its persistency, is usually the highly dominating isomer (Bernhoft et al, 1997;Bentzen et al, 2008b), while dominating levels of a-HCH in tissues of wild animals were measured only in areas close to land in agricultural use, where technical mixtures of HCHs were used recently (Tomza-Marciniak et al, 2014). Christensen et al (2005) also reported domination of several more volatile pesticides, including P HCH and HCB, in contaminant profiles of interior grizzly bears consuming a higher proportion of terrestrial vegetation.…”
Section: Discussionsupporting
confidence: 84%
“…A similar dominance of higher chlorinated PCBs was observed in studies on other terrestrial mammals Gamberg and Braune, 1999;Shore et al, 2001;Christensen et al, 2005;Polder et al, 2009;Tomza-Marciniak et al, 2014).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations